Asian diaspora and East-West modernity - Ma, Sheng-mei (Comparative cultural studies., 2012)
In this book, Asian Diaspora and East-West Modernity, Sheng-mei Ma analyzes Asian, Asian diaspora, and Orientalist discourse and probes into the conjoinedness of West and East and modernity's illusions. Drawing from Anglo-American, Asian American, and Asian literature, as well as J-horror and manga, Chinese cinema, the internet, and the Korean Wave, Ma's analyses render fluid the two hemispheres of the globe, the twin states of being and nonbeing, and things of value and nonentity. Suspended on the stylistic tightrope between research and poetry, critical analysis and intution, Asian Diaspora restores affect and heart to diaspora in between East and West, at-homeness and exilic attrition. Diaspora, by definition, stems as much from socioeconomic and collective displacement as it points to emotional reaction. This book thus challenges the fossilized conceptualizations in area studies, ontology, and modernism.